Concerted cellular responses to type I interferon propel memory impairment associated with amyloid β plaques. (December 2021) - Roy, Ethan; Chiu, Gabriel; Li, Sanming; Zheng, Hui; Cao, Wei
Abstract: Background: Despite well‐documented maladaptive neuroinflammation in Alzheimer's disease (AD), the principal signal that drives memory and cognitive impairment remains elusive. Type I interferon (IFN) is an innate immune cytokine aberrantly elicited by β amyloid plaques. Here, we seek to understand its role in cognition and neuropathology relevant to AD. Method: We introduced a genetically‐encoded IFN‐responsive reporter system into 5XFAD mice, a β‐amyloid plaque model, to gauge IFN‐stimulated cellular response. We administered an antibody that specifically blocks the signaling of IFN receptor into 5XFAD mice and examined their memory performance, neuropathologies, and gene expression. Moreover, we generated and analyzed 5XFAD mice that lack IFN receptor selectively in microglia or neural cells. Result: Here, we reveal an age‐dependent, brain‐wide, and profound accrual of brain cells responding to IFN signaling activation in 5XFAD mice. Long‐term blockade of IFN receptor rescued both memory and synaptic deficits, and also resulted in reduced microgliosis, inflammation, and neuritic pathology. Interestingly, microglia‐specific IFN receptor ablation attenuated the loss of post‐synaptic terminals, whereas IFN signaling in neural cells contributed to pre‐synaptic alteration and plaque accumulation. Intriguingly, IFN pathway activation displayed a strong inverse correlation with cognitive performance, promoting selective synapse engulfment by microglia rather than amyloid plaques. Conclusion: IFN signaling represents a critical module within the neuroinflammatory network of AD and prompts a concerted cellular state that is detrimental to memory and cognition.